Extraction of Silica Nanoparticles from Rice Husk Ash (RHA) and Study of Its Application in Making Composites - Raut, Bimal Kumar; Panthi, Khim Prasad (Journal of Nepal Chemical Society, 2019)
Nanotechnology is the most emerging field in the area of different scientific research. Various methods of synthesis of nanoparticles are available. The wet chemical synthesis method is applicable in the extraction of silica nanoparticles from Rice Husk Ash (RHA). Rice husk is a form of waste product from the rice milling industries which is produced in an abundance amount in and around the country. Rice husk which is generally left on the field as a waste contains 60% silica content and can be economically viable raw materials for the extraction of silica [1-2]. Initially, Rice husk was burnt to obtain its ash. Then, a simple bottom-up approach, the sol-gel method was applied, and fine powder silica in the nanoscopic range was extracted. After extraction of it, internal arrangement and average particle size were recognized by XRD while molecular components and structure present in silica were identified by FTIR. The obtained silica was then used in making of ceramics matrix nanocomposites (particularly silica-sand cement block), and its mechanical properties were identified by compressive strength test using Instron testing machine which was found to be increased in comparing with the compressive strength of ceramics composite (Sand cement block) prepared in the same ratio and same size of mold as that of ceramics matrix nanocomposites. The ceramics matrix nanocomposites acquiring higher mechanical strength than Ceramics composite occurred due to the incorporation of Silica nanoparticles.